2018
DOI: 10.1016/j.jvs.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde popliteal access to treat femoropopliteal artery occlusive disease

Abstract: RPA access had lower technical success and primary patency compared with antegrade access at 6 months. There were no differences demonstrated between the two access techniques in perioperative morbidity and mortality or 6-month amputation, MALE, and survival. This technique should be considered when CFA access cannot be accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Since that time there have been several case reports and single-center series describing this technique. [4][5][6][7][8] A prospective, nonrandomized, multicenter study reported outcomes only to 30 days. 9 Because the early success by pioneers and centers of excellence may not be replicated in real-world practice, this study analyzed the real-world use and outcomes of retrograde pedal access for peripheral vascular interventions (PVI) in patients with CLTI enrolled in a multicenter national quality improvement registry.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time there have been several case reports and single-center series describing this technique. [4][5][6][7][8] A prospective, nonrandomized, multicenter study reported outcomes only to 30 days. 9 Because the early success by pioneers and centers of excellence may not be replicated in real-world practice, this study analyzed the real-world use and outcomes of retrograde pedal access for peripheral vascular interventions (PVI) in patients with CLTI enrolled in a multicenter national quality improvement registry.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,14,17,18 The 84.5% POA technical success rate was also similar to that of other studies, which reported a range between 80% and 100%. 9,12,15,16,19 This large range in POA technical success can be partly attributed to the wide variability in technique, which has included prone and/or supine patient positioning and differing usage of duplex guidance. 9,11,12,16,19 Although our study did not observe a statistically significant association between dialysis and technical success, dialysis was included as a forced variable in the multivariate regression model for technical failure due to its established association with inferior endovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,10,13,14 In contrast, the use of retrograde POA has been noted to provide superior pushability and torquability in comparison to femoral access and may facilitate easier crossing of lesions through the softer distal cap of the occlusive atherosclerotic plaque. 9,[11][12][13]15 Recent improvements in technique have also decreased the rates of complications associated with early POA attempts. 9,16 However, the lack of a standardized POA protocol; inherent risks associated with the prone position; and difficulties associated with accessing a flexed leg, compressing the vessel after sheath removal, and obesity complicate the POA approach.…”
Section: Introductionmentioning
confidence: 99%
“…Despite various retrograde techniques reported in the literature, a below-knee access might be challenging, especially in patients with CLI, because vessels are typically small and diseased 2, 3. Not infrequently, severe arterial spasm that necessitates the need for vasodilators, such as nitroglycerin or papaverine, can occur 1, 4.…”
Section: Discussionmentioning
confidence: 99%
“…Not infrequently, severe arterial spasm that necessitates the need for vasodilators, such as nitroglycerin or papaverine, can occur 1, 4. Not surprisingly, retrograde tibial or pedal access is reported to have lower technical success and primary patency rates compared with antegrade femoral access 2, 4. In some complicated CLI cases, the technical success rate was reported to be as low as 63.5%, 5 and devastating complications have been reported 3, 6.…”
Section: Discussionmentioning
confidence: 99%